Evidence for Early (> 44 Ma) Himalayan Crustal Thickening, Tethyan Himalaya, southeastern Tibet - Aikman, Amos B.; Harrison, T. Mark; Lin, Ding (Earth and planetary science letters, 2008)
Comprehensive understanding of Himalayan orogenesis is limited in part by a poor knowledge of the Eohimalayan episode; a phase of tectonic activity predating the better understood Neohimalayan crustal thickening associated with coaxial deformation along the Main Central thrust. The Cambo–Ordovician to Tertiary metasedimentary sequences outcropping within the Tethyan Himalaya are the structurally highest units of the Himalayan Fold and Thrust Belt; they and are inferred to have been the first to have accreted to Asia. A compilation of data from transects along the length of the main Himalayan arc shows that the Tethyan sequences have experienced at least five deformation events, although the timing of these episodes is poorly constrained. Emplacement of a series of undeformed granitoid bodies following the second of these events, which accounts for the majority of crustal thickening in the Tethyan Himalayan units, is constrained by U–Pb zircon dating to be older than 44.1 ± 1.2 Ma. Thus, significant crustal thickening had occurred along the length of the proto-Himalayan arc by the mid-Eocene, or within 10 to 20 myr of the initiation of Himalayan orogenesis.